DETERMINING LITERARY LANGUAGE AND LINGUOCULTURAL CHARACTERISTICS IN PROSE WORKS - Rahmatullayeva Nigora Erkinpulatovna, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The age of globalization puts before the science of linguistics, like other sciences, the task of solving new problems. One such problem is the study of the language system based on the principles of the anthropocentric paradigm. Today, the emergence of the anthropocentric trend is considered a fundamental turning point in linguistics, and many studies have been and are being created in this regard. The anthropocentric paradigm "does not study language as a dry structure but as an open system based on living dialogue and communication.